Comparative analysis of roundscad dried in polythene drier and under direct sunlight. - Kampitan, Ma. Cristina R. (Miagao, Iloilo College of Fisheries, University of the Philippines, 1980)
The use of polythene tent driers, shortens drying time and produces dried round scad (Decappterus macrosoma Beuker) of low moisture content compared to that of direct sun-drying. Its low moisture content produced a sigmoidal curve upon determining the relationship of its water activity and reative humidity in the sorption isotherm; and the growth of the microorganisms and molds were inhibited. Also, it produced a product of superior quality with regards to its color, odor, texture and taste. The shelf lives of these products were prolonged for 3 to 4 weeks at room temperature before mold growth was evident. On the other hand; sun dried roundscad stored for a week at room temperature was evident of yeasts and molds.
Keywords: Fish-Preservation.